Analysis Of The Effect Of Production Input On Corn Farming Income In Ranah Batahan District West Pasaman Regency - Rosi Permata Sari; Nofrianil Nofrianil (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Purpose: The purpose of thes study is to analyze the effect of land area, seed costs, fertilizer costs, pesticide costs, and labor costs simultaneously and partially on corn farming income in Ranah Batahan District, West Pasaman Regency. Methodology: The study was conducted in February 2025 using quantitative data. Sample of 93 farmers was calculated using the Slovin formula and selected using the Proportionate Stratified Random Sampling method. Data analysis with the classical assumption test, multiple linear regression, statistical, and coefficient of determination (R²). Results: Land area, seed cost, fertilizer cost, pesticide cost, and labor cost simultaneously have significant effect on income with a significance value of 0.000. Partially land area, fertilizer cost, and pesticide cost have significant effect with a significance level of ≤0.05, while seed cost and labor cost do not have significant effect on corn farming income with a significance level of ≥0,05. The coefficient of determination of 41.4% indicates the variables in the study can explain farming income. Findings: Land area increases corn farmers' income, while high fertilizer costs reduce profits. Pesticide costs have a positive impact indicating the importance of pest control, while the insignificance of seed and labor costs indicates suboptimal input utilization. Novelty: This study analyzes the influence of production inputs for corn farming in Ranah Batahan District, focusing on specific local conditions that are rarely discussed in previous studies. Originality: This study offers the effectiveness of input use in increasing corn farmers' income. Conclusion: Production input from land area, fertilizer costs, and pesticide costs are important factors that affect corn farming income. Type of Paper: This article is the result of quantitative research that is explanatory in nature with a multiple linear regression approach.